1 / 9

90 likes | 229 Views

Lesson 3-7. Higher Order Deriviatives. Objectives. Find second and higher order derivatives using all previously learned rules for differentiation. Vocabulary. Higher order Derivative – taking the derivative of a function a second or more times. Example 1.

Download Presentation
## Lesson 3-7

**An Image/Link below is provided (as is) to download presentation**
Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.
Content is provided to you AS IS for your information and personal use only.
Download presentation by click this link.
While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.
During download, if you can't get a presentation, the file might be deleted by the publisher.

E N D

**Lesson 3-7**Higher Order Deriviatives**Objectives**• Find second and higher order derivatives using all previously learned rules for differentiation**Vocabulary**• Higher order Derivative – taking the derivative of a function a second or more times**Example 1**Find second derivatives of the following: • y = 5x³ + 4x² + 6x + 3 • y = x² + 1 y’(x) = 15x² + 8x + 6 y’’(x) = 30x + 8 y’(x) = ½ (x² + 1)-½ (2x) = x / (x² + 1)½ (1)(x² + 1)½ - x ½ (x² + 1) -½ (2x) y’’(x) = -------------------------------------------- (x² + 1)**Example 2**Find the fourth derivatives of f(x) = (1/90)x10 + (1/60)x5 Find a formula for f n(x) where f(x) = x-2 f’(x) = (10/90)x9 + (5/60)x4 f’’(x) = (90/90)x8 + (20/60)x3 f’’’(x) = (720/90)x7 + (60/60)x2 F’’’’(x) = (5040/90)x6 + (120/60)x = 56x6 + 2x f’(x) = (-2)x-3 f’’(x) = (-2)(-3)x-4 f’’’(x) = (-2)(-3)(-4)x-5 f’’’’(x) = (-2)(-3)(-4)(-5)x-6 fn(x) = (-1)n(n+1)! x-(2-n)**Example 3**Find the third derivatives of the following: y = (3x³ - 4x² + 7x - 9) f(x) = e2x+7 y’(x) = 9x² - 8x + 7 y’’(x) = 18x - 8 y’’’(x) = 18 f’(x) = 2e2x+7 f’’(x) = 4e2x+7 f’’’(x) = 8e2x+7**Chain Rule Revisited**FunctionDerivativeFunctionDerivative y = xn y’ = n xn-1 y = un y’ = n un-1 u’ y = ex y’ = ex y = eu y’ = u’ eu y = sin x y’ = cos x y = sin u y’ = u’ cos u y = cos x y’ = -sin x y = cos u y’ = -u’ sin u y = tan x y’ = sec² x y = tan u y’ = u’ sec² u y = cot x y’ = -csc² x y = cot u y’ = u’ csc² u where u is a function of x (other than just u=x) and u’ is its derivative**Derivatives FAQ**• When do I stop using the chain rule?Answer: when you get something that you can take the derivative of without having to invoke the chain rule an additional time (like a polynomial function). • Does the argument in a trig function ever get changed?No. The item (argument) inside the trig function never changes while taking the derivative. • Does the exponent always get reduced by one when we take the derivative?Only if the exponent is a constant! If it is a function of x, then it will remain unreduced and you have to use another rule instead of simple power rule. • When do I use the product and quotient rules?Anytime you have a function that has pieces that are functions of x in the forms of a product or quotient.**Summary & Homework**• Summary: • Derivative of Derivatives • Use all known rules to find higher order derivatives • Homework: • pg 240 - 242: 5, 9, 17, 18, 25, 29, 49, 57

More Related